2016
DOI: 10.1186/s40337-016-0126-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between unhealthy dieting behaviors and tobacco use among adolescents

Abstract: BackgroundCigarette smoking is an important risk factor for unhealthy dieting behaviors (UDBs) in youth. The role of alternative tobacco products and UDB engagement has yet to be examined empirically despite concerning trends in use. This study aimed to examine UDB prevalence in a U.S. geographic region-specific adolescent sample and associations with a variety of tobacco use behaviors and perceptions.MethodsWeighted data from the 2013 Virginia Youth Survey were analyzed (n = 6903). UDBs assessed included past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
(40 reference statements)
0
19
0
1
Order By: Relevance
“…A secondary data analysis was conducted using publicly available, de-identified data of 6935 high school students aged 12 or older from the 2013 Virginia Youth Survey (VYS; Virginia Department of Health, 2016; see Jones, Wiseman, & Kharitonova, 2016; Nasim, Blank, Berry, & Eissenberg, 2012; Sutter, Nasim, Veldheer, & Cobb, 2016) for other representative publications using this dataset mechanism). A two-stage cluster sample design was used to obtain a representative student sample in grades 9–12.…”
Section: Methodsmentioning
confidence: 99%
“…A secondary data analysis was conducted using publicly available, de-identified data of 6935 high school students aged 12 or older from the 2013 Virginia Youth Survey (VYS; Virginia Department of Health, 2016; see Jones, Wiseman, & Kharitonova, 2016; Nasim, Blank, Berry, & Eissenberg, 2012; Sutter, Nasim, Veldheer, & Cobb, 2016) for other representative publications using this dataset mechanism). A two-stage cluster sample design was used to obtain a representative student sample in grades 9–12.…”
Section: Methodsmentioning
confidence: 99%
“…However, unhealthy lifestyles are increasingly prevalent among adolescents, leading to negative consequences on their health over time 3,4 . Unhealthy behaviors such as insufficient physical activity, prolonged screen time use, 5 unhealthy diet, alcohol and tobacco consumption, 6,7 sleeping problems, 8 drug use, 9 and unsafe sex 10 are all associated with adverse health outcomes. As some of these behaviors are interrelated and could drive further psychosocial problems, 11 studying them from a holistic perspective might be relevant, attempting to understand adolescents' behaviors as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Sutter et al (2016) found that extreme dieting behaviors (e.g., fasting, vomiting, laxatives or diet pills, liquids, powders) were proportionally more frequent among 12-to 18-year-old smokeless tobacco users, yet the study investigated a heterogeneous and broader range of SLT products (e.g., dip, chewing tobacco), making it difficult to specify conclusions. Sutter et al (2016) found that extreme dieting behaviors (e.g., fasting, vomiting, laxatives or diet pills, liquids, powders) were proportionally more frequent among 12-to 18-year-old smokeless tobacco users, yet the study investigated a heterogeneous and broader range of SLT products (e.g., dip, chewing tobacco), making it difficult to specify conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have investigated the associations between SLT use, disordered eating, and weight concerns. Sutter et al (2016) found that extreme dieting behaviors (e.g., fasting, vomiting, laxatives or diet pills, liquids, powders) were proportionally more frequent among 12-to 18-year-old smokeless tobacco users, yet the study investigated a heterogeneous and broader range of SLT products (e.g., dip, chewing tobacco), making it difficult to specify conclusions. Root et al (2010) investigated patterns of comorbidity of ED and substance use behaviors in the Swedish Twin Registry.…”
Section: Introductionmentioning
confidence: 99%